[1, 5]-Proton transfer as a key strategy: Rapid access to natural product-inspired library of 3-pyrazolyl isoflavones. Issue 37 (11th September 2020) - Li, Zheng; Feng, Ting-Ting; Zhou, Ying; Tian, You-Ping; Zhou, Wei; Liu, Xiong-Li
Abstract: Inspired by the chemistry and biology of isoflavones and pyrazolones, herein we report the first example of synthesis of 3-pyrazolyl isoflavones by two steps, starting from commercially available chromanones and pyrazolones. The [1, 5]-proton transfer was used as a key strategy. All the 3-pyrazolyl isoflavones 3, which are hard to synthesize by traditional methods, are smoothly obtained in up to 86% total yield. Interestingly, the product forms a stable 7-membered ring through intramolecular hydrogen bond between carbonyl group on chromone core and hydroxyl group on pyrazolone core, preventing further ketone-enol tautomerization. In particular, the products are featured with an intriguing combination of two privileged motifs including isoflavone and pyrazolone substructures, which might be valuable in medicinal chemistry. Graphical abstract: Image 1 Highlights: The first example of synthesis of 3-pyrazolyl isoflavones. [1, 5]-hydrogen transfer as the key step. Potential biologically active molecules.